Analisis anggaran biaya dan penjadwalan pada gedung serbaguna dusun hulung, kecamatan leihitu, maluku tengah - Gaspersz, Willem; Apalem, Delvia Rimesye; Rumbia, La Randi (JURNAL SIMETRIK, 2025)
The Cost Budget Plan is a tool to control the amount of cost of completing work sequentially as planned. The purpose of this study is to determine the difference in the comparison of the cost budget plan and using the Basic Price of the Maluku Provincial PU Service on December 23, 2019, AHSP SNI 2016 and AHSP SNI 2013 using the time schedule method and the CPM method and to find out how much the difference in the construction work cost price between the implementing consultant using AHSP SNI 2013 with the author in the Hulung Hamlet multipurpose building, Leihitu District, Central Maluku Regency. This study aims to find out the results of the cost comparison, in calculating the comparative budget plan for the construction of a multi-purpose building using the basic price of Maluku Province 2019 and using the analysis of AHSP SNI 2016 with AHSP SNI 2013. The difference obtained was Rp. 1,050,900,000.00, the comparison results obtained in this writing were Rp. 3,245,800,000.00 and from the consultant it was Rp. 4,282,500,000.00 Keywords: AHSP Comparison, S Curve, SNI 2013, CPM